2022
DOI: 10.3390/jcm11113153
|View full text |Cite
|
Sign up to set email alerts
|

Drugs and Vaccines Hypersensitivity in Children with Mastocytosis

Abstract: Mastocytosis, a heterogeneous mastcell disease, include three different entities: cutaneous mastocytosis, systemic mastocytosis (SM) and mast-cell sarcoma. Tryptase levels can differentiate cutaneous mastocytosis from SM. In mastocytosis, quick onset drug hypersensitivity reactions (DHRs) that are facilitated by mastcell mediators, are investigated in adults. Due to the limited number of children with mastcell disease and increased serum tryptase levels, the role of drugs in this age group is less studied. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…Physical or mechanical factors are at least equally significant in provoking mast cell degranulation during anesthesia. Because anaphylaxis in children with mastocytosis is most commonly idiopathic, the role of drugs is overestimated [ 62 ]. Some studies have reported a higher risk of DIA in children with systemic illnesses, most often malignancies, storage diseases, cardiovascular diseases, seizure disorders, renal diseases, coagulation abnormalities, and rheumatologic diseases, and/or taking other medications [ 56 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Physical or mechanical factors are at least equally significant in provoking mast cell degranulation during anesthesia. Because anaphylaxis in children with mastocytosis is most commonly idiopathic, the role of drugs is overestimated [ 62 ]. Some studies have reported a higher risk of DIA in children with systemic illnesses, most often malignancies, storage diseases, cardiovascular diseases, seizure disorders, renal diseases, coagulation abnormalities, and rheumatologic diseases, and/or taking other medications [ 56 ].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Conflicting results were reported as to whether bST by itself, or as a correlate of mastocytosis or other mast cell related conditions, is a predictor of systemic reactions including drug hypersensitivity [30 ▪▪ ,31,32]. Few pediatric series are available, and systemic mastocytosis is less frequent than cutaneous mastocytosis; however, a recent study reported a lack of association between high bST levels and the occurrence of drug hypersensitivity reactions among children with mastocytosis [33]. Also in a pediatric case, transient increase in aST over bST was reported following the NSAID diclofenac administration as a suppository [34].…”
Section: Serum Tryptase and Drug Hypersensitivity: How?mentioning
confidence: 99%
“…DA to quinolones, vancomycin, aminoglycosides, and tetracyclines are rare except in children with cystic fibrosis and chronic diseases with repeated antibiotic exposures 23,172 . Less than 20% of children with a reported history of NSAIDs hypersensitivity had the diagnosis confirmed through challenge 23,100,172,174–177 …”
Section: Drug Allergy In Childrenmentioning
confidence: 99%
“…General anesthesia agents and opioid analgesics are a significant cause of DA in hospitalized children and children who had undergone a general anesthesia had more than six times the risk of developing an adverse drug reaction 100,177 …”
Section: Drug Allergy In Childrenmentioning
confidence: 99%
See 1 more Smart Citation